Coarsening and percolation in the kinetic 2d Ising model with spin exchange updates and the voter model. (8th August 2018) - Tartaglia, Alessandro; Cugliandolo, Leticia F; Picco, Marco
Abstract: We study the early time dynamics of bimodal spin systems on 2d lattices evolving with different microscopic stochastic updates. We treat the ferromagnetic Ising model with a locally conserved order parameter (Kawasaki dynamics), the same model with a globally conserved order parameter (non-local spin exchanges), and the voter model. As already observed for non-conserved order parameter dynamics (Glauber dynamics), in all the cases in which the stochastic dynamics satisfy detailed balance, the critical percolation state persists over a long period of time before usual coarsening of domains takes over and eventually takes the system to equilibrium. By studying the geometrical and statistical properties of time-evolving spin clusters we are able to identify a characteristic length, different from the usual length that describes the late time coarsening, which is involved in all scaling relations in the approach to the critical percolation regime. We find that this characteristic length depends on the particular microscopic dynamics and the lattice geometry. In the case of the voter model, we observe that the system briefly passes through a critical percolation state, to later approach a dynamical regime in which the scaling behaviour of the geometrical properties of the ordered domains can be ascribed to a different criticality.